2009
DOI: 10.1007/s11244-009-9295-0
|View full text |Cite
|
Sign up to set email alerts
|

H/D Exchange on Silica-Grafted Tantalum(V) Imido Amido [(≡SiO)2Ta(V)(NH)(NH2)] Synthesized from Either Ammonia or Dinitrogen: IR and DFT Evidence for Heterolytic Splitting of D2

Abstract: The silica-grafted Ta (V) imido amido complex [(:SiO) 2 Ta(NH)(NH 2 )], 2, obtained from the reaction of either ammonia or dinitrogen plus hydrogen with the silicagrafted hydrides [(:SiO) 2 Ta (III) H], 1a, and [(:SiO) 2-Ta (V) H 3 ], 1b, undergoes H/D exchange with D 2 . In situ IR spectroscopy shows that the fully labelled compound [(:SiO) 2 Ta(ND)(ND 2 )], 2-d, can be obtained by moderate heating (60°C, 3 h) under D 2 atmosphere (550 torr, 300 eq. with respect to Ta), and that the exchange is reversible. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 74 publications
6
24
0
Order By: Relevance
“…This behaviour has been observed through the appropriate isotopic shifts in the IR spectra of the complexes and is reversible, since exposing the deuterated species to a hydrogen atmosphere regenerates the original imido amido species. [63] The mechanism of this exchange reaction has been explored by DFT calculations on the model cluster compound [{(μ-O)(HO) 2 SiO} 2 Ta V (NH)(NH 2 )] (Figure 5b), with the Gaussian 03 package. [63] Heterolytic splitting of H 2 is the most favoured pathway.…”
Section: Reactivity and Mechanism Of Formation Of Silica-supported Tamentioning
confidence: 99%
See 3 more Smart Citations
“…This behaviour has been observed through the appropriate isotopic shifts in the IR spectra of the complexes and is reversible, since exposing the deuterated species to a hydrogen atmosphere regenerates the original imido amido species. [63] The mechanism of this exchange reaction has been explored by DFT calculations on the model cluster compound [{(μ-O)(HO) 2 SiO} 2 Ta V (NH)(NH 2 )] (Figure 5b), with the Gaussian 03 package. [63] Heterolytic splitting of H 2 is the most favoured pathway.…”
Section: Reactivity and Mechanism Of Formation Of Silica-supported Tamentioning
confidence: 99%
“…[63] The mechanism of this exchange reaction has been explored by DFT calculations on the model cluster compound [{(μ-O)(HO) 2 SiO} 2 Ta V (NH)(NH 2 )] (Figure 5b), with the Gaussian 03 package. [63] Heterolytic splitting of H 2 is the most favoured pathway. This involves protonation of either the imido or amido ligand through a transient dihydrogen adduct and simultaneous hydride migration onto the tantalum centre ( Figure 6).…”
Section: Reactivity and Mechanism Of Formation Of Silica-supported Tamentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Further studies on the reactivity of complex 2 showed its capacity to react with the H–H bond of H 2 and the N–H bond of ammonia. Both reactions occur across the Ta–N and Ta=NH bonds of 2 via heterolytic bond cleavage 13,16 …”
Section: Introductionmentioning
confidence: 99%